ANALISIS PERKEMBANGAN KARAKTER TOKOH UTAMA DALAM NOVEL SEPORSI MIE AYAM SEBELUM MATI KARYA BRIAN KHRISNA - Uji Saputri; Elsa Mulya Karlina (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to analyze the character development of the main character in the novel Seporsi Mie Ayam Sebelum Mati by Brian Khrisna. The primary focus of this research is on the psychological journey of the character Ale, who experiences depression and loss of hope throughout the narrative. The method employed is a qualitative approach with library research, relying on text analysis and relevant literary theories to provide a comprehensive understanding of the character's evolution. The findings reveal that Ale undergoes significant transformation from emotional alienation and despair to self-acceptance and positive social interaction. This process reflects the importance of social support and self-awareness in effectively addressing mental health issues. Additionally, this study uncovers how Ale's traumatic experiences and social pressures shape his personality and influence his decisions. Thus, the novel not only depicts an individual's struggle against depression but also conveys a profound moral message about the importance of self-acceptance and social interaction in facing life's challenges. This research is expected to make a meaningful contribution to the understanding of mental health issues within the context of contemporary Indonesian literature.